Conjugated Polyvinyl Alcohol Modified SnO2 for Efficient Visible Light Photocatalytic Reduction of Cr(VI) - Chen, Shaojie; Luo, Yuanyuan; Xu, Yuhan; Chen, Ying; Jiang, Yinxing; Li, Zhao; Tian, Lin; Wang, Furong; Liu, Yuanyuan; Li, Jing (Bulletin of Chemical Reaction Engineering & Catalysis, 2024)
The photocatalytic activity of tin dioxide (SnO2) is limited due to its inadequate response to the solar spectrum, wide band gap, and low visible light photocatalytic activity. Here, we synthesized conjugated polyvinyl alcohol (CPVA) modified tin dioxide (CPVA/SnO2) through in-situ hydrothermal synthesis and evaluated its performance for photocatalytic reduction of hexavalent chromium Cr(VI). A series of testing and characterization results revealed that CPVA was uniformly coated on the surface of SnO2, forming a mesoporous CPVA/SnO2 heterojunction with enhanced crystallinity and reduced oxygen defects, which resulted in an expanded light absorption range towards the red light region. The reaction rate constant of CPVA/SnO2-A for photocatalytic reduction of Cr(VI) under visible light (0.060 min-1) was 6 times higher than that of homemade CPVA/TiO2 and 2.87 times higher than that of SnO2 for the photocatalytic reduction of Cr(VI) under UV light (0.0209 min-1). The photocatalytic mechanism indicates that CPVA/SnO2 exhibited significantly enhanced performance under UV-light irradiation by forming a type II heterojunction. When CPVA/SnO2 was exposed to visible light, photogenerated electrons on the lowest unoccupied molecular orbital (LUMO) of CPVA were efficiently transferred to the surface of SnO2 through the CPVA/SnO2 heterojunction, reducing electron-hole recombination while also photosensitizing the photocatalyst and promoting efficient photocatalysis under visible light illumination. Ultimately, this process effectively reduces Cr(VI) to Cr(III). Copyright © 2024 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).